Pain Scales in Neonates Receiving Mechanical Ventilation in Neonatal Intensive Care Units – Systematic Review - Popowicz H; Kwiecień-Jaguś K; Olszewska J; Mędrzycka-Dąbrowska WA (Journal of Pain Research, 2020)
Hanna Popowicz,1 Katarzyna Kwiecień-Jaguś,2 Jolanta Olszewska,1 Wioletta A Mędrzycka-Dąbrowska2 1Department of Obstetric and Gynaecological Nursing, Medical University of Gdansk, Gdansk, Poland; 2Department of Anaesthesiology Nursing and Intensive Care, Medical University of Gdansk, Gdansk, PolandCorrespondence: Wioletta A Mędrzycka-DąbrowskaDepartment of Anaesthesiology Nursing and Intensive Care, Medical University of Gdansk, Dębinki Str.7, 80-211 Gdansk, PolandEmail wioletta.medrzycka-dabrowska@gumed.edu.plIntroduction: Recently, interest in the problem of proper prevention and monitoring of pain, especially acute, has been increasing in relation to various age groups. Greater awareness of the problem prompts discussion about the purpose of analgesia in newborns treated with mechanical ventilation.Aim: The purpose of the systematic review was to analyze current research on the use of pain scales in newborns treated with mechanical ventilation in the Neonatal Intensive Care Unit.Methods: Medline databases: PubMed, OVID, EBSCO, Web of Science and Cochrane Library were traced using the appropriate keywords. The search was limited to studies in English. The review took into account the years 2006– 2019. Considering the criteria, 12 articles were included in further analysis, to which full access was obtained.Results: The analyzed scientific research showed differences in beliefs about the validity and credibility of the scales used. Researchers indicated that staff with practical experience in using scales in their daily practice was very skeptical of the results obtained on their basis.Conclusion: Based on this review, no explicit evidence can be obtained to support the use of one proper scale in pain assessment. It can be inferred that the COMFORT and N-PASS scales are effective for pain assessment and for determining the need for analgesics in mechanically ventilated neonates. These scales may be equally effective in assessing chronic pain, especially in mechanically ventilated children. On the other hand, the PIPP and CRIES scales are most commonly recommended for assessing acute and postoperative pain.Keywords: pain, scales, newborn, NICUs